PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. ARKA MAHESA PRATAMA DI JAKARTA SELATAN - salis rabindra ishaya (JURNAL LENTERA BISNIS, 2017)
ABSTRACT This study was conducted to determine how much Effect of Motivation on Employee Productivity PT. Arka Mahesa Pratama. This study uses regression kauntitatif using the formula to see Effect of Motivation on Employee Productivity PT. Arka Mahesa Pratama. The study population was only staff employees who work in PT. Arka Mahesa Pratama totaling 40 people and sampled in this study as many as 35 people. With the technique of sampling using a questionnaire, each respondent was given as many as 20 questions using a Likert scale. The results of data processing show that Influence Motivation on Employee Productivity PT. Arka Mahesa Pratama is strong, it means that relations between the two variables are significant at a strong degree of confidence. This shows that the higher the motivation gained more and more satisfied employees. Keywords: Motivation, Productivity, Employee